2010
DOI: 10.1128/jvi.00917-09
|View full text |Cite
|
Sign up to set email alerts
|

ICP27 Phosphorylation Site Mutants Are Defective in Herpes Simplex Virus 1 Replication and Gene Expression

Abstract: Herpes simplex virus 1 (HSV-1) protein ICP27 is a multifunctional regulatory protein that is posttranslationally modified by phosphorylation during viral infection. ICP27 has been shown to be phosphorylated on three serine residues, specifically serine residues 16 and 18, which are within casein kinase 2 (CK2) sites, and serine residue 114, which is within a protein kinase A (PKA) site. Phosphorylation is an important regulatory mechanism that is reversible and controls many signaling pathways, protein-protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…For instance, ICP27 phosphorylation is required for its interaction with the cellular RNA export factors REF and TAP/p15 as well as for efficient HSV-1 replication (10,11). Analogously, we showed that proper subcellular localization and efficient mRNA export of HCMV pUL69 were dependent on the catalytic activity of the viral serine/threonine protein kinase pUL97 or the cellular kinase orthologs CDK1, -2, -7, and -9 (12,13).…”
Section: Importancementioning
confidence: 56%
“…For instance, ICP27 phosphorylation is required for its interaction with the cellular RNA export factors REF and TAP/p15 as well as for efficient HSV-1 replication (10,11). Analogously, we showed that proper subcellular localization and efficient mRNA export of HCMV pUL69 were dependent on the catalytic activity of the viral serine/threonine protein kinase pUL97 or the cellular kinase orthologs CDK1, -2, -7, and -9 (12,13).…”
Section: Importancementioning
confidence: 56%
“…Therefore, the flexibility of this region may be required for ICP27 to undergo successive interactions with proteins and RNA. Interestingly, the phosphorylation site mutants, which were found to be even more disordered than wild-type ICP27, were severely impaired in their ability to interact with proteins that interact with wild-type ICP27 (6,33). Despite the effects on protein interactions, the phosphorylation site mutants were able to bind gC sequences with the same affinity and specificity as those of wild-type ICP27 (6).…”
Section: Discussionmentioning
confidence: 93%
“…Phosphorylation of YY1 by CKII␣ prevents cleavage by caspase-7 during apoptosis (66). CKII phosphorylation during virus infection plays an important role in regulation of ICP27 and EB2 binding activities to cellular cofactors and promotes virus replication of HSV-1 and EBV (63,67,68). ORF57 and its homologues are self-interacting proteins via their C-terminal domains (41,47,50).…”
Section: Discussionmentioning
confidence: 99%